A novel functional IKBKE variant activating NFAT in a patient with polyarthritis and a remittent fever - Yamada, Saeko; Nagafuchi, Yasuo; Yamada, Mamiko; Suzuki, Hisato; Natsumoto, Bunki; Ota, Mineto; Takazawa, Ikuo; Hatano, Hiroaki; Kono, Masanori; Harada, Hiroaki; Shoda, Hirofumi; Okamura, Tomohisa; et al. (Frontiers in Immunology, 2024)
Background IKBKE is a negative regulator of T cell activation and one of the key activators of type I interferon (IFN) and NFκB signaling via non-classical pathways. The upstream single nucleotide polymorphism of IKBKE (rs2297550-G) is a genome-wide association study risk variant of systemic lupus erythematosus, and is associated with decreased IKBKE expression in T cells by expression quantitative trait locus analysis. Case presentation A 48-year-old female had a remittent fever, arthritis, and oral ulcers for 20 years. She had a poor response to corticosteroids or disease-modifying antirheumatic drugs, including the tumor necrosis factor-α antagonist, etanercept, and the anti-interleukin-6 receptor antibody, tocilizumab. Method She participated in the Initiative on Rare and Undiagnosed Disease (IRUD), and whole-exome sequencing (WES) was performed. Functional analyses were conducted by transfecting the identified variants into reporter cells to assess the activation of NFAT and NFκB signaling. Additionally, peripheral blood RNA- sequencing (RNA-seq) data were compared with those from healthy individuals to evaluate the gene expression profiles of immune cells. Result WES identified a novel heterozygous c.1877G>A, p(Cys626Tyr) variant in IKBKE. Functional analysis indicated that this variant led to increased activity of NFAT (p = 0.015) and decreased activity of NFκB and type I IFN (p = 0.00068 and 0.00044, respectively). The patient had a remarkably low proportion of Naïve CD4 T cells. RNA-seq of peripheral blood immune cell subsets revealed significant differences in gene expression, especially in T cells. Conclusion A novel functional heterozygous variant in IKBKE is described in a patient with a remittent fever and arthritis. The data suggest that IKBKE is an important negative regulator of inflammation, particularly in T cells, and this IKBKE variant might be the underlying cause of a novel autoinflammatory pathology.